2017
DOI: 10.1016/j.mce.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles: Inflammatory and haemostatic biomarkers in Polycystic Ovary Syndrome

Abstract: Polycystic Ovary Syndrome (PCOS) is associated with a chronic low-grade inflammation and predisposition to hemostatic and atherosclerotic complications. This case-control study evaluated the microparticles (MPs) profile in patients with the PCOS and related these MPs to clinical and biochemical parameters. MPs derived from platelets (PMPs), leuckocytes (LMPs) and endothelial cells (EMPs) were evaluated, as well as MPs expressing tissue factor (TFMPs), by flow cytometry, comparing women with PCOS (n = 50) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
0
15
1
1
Order By: Relevance
“… 7 15 16 Chronic inflammation also contributes to endothelial dysfunction, exacerbating the development of atherosclerotic plaques, triggering the onset of CVD. 17 As such inflammation has been associated with both CVD and coronary artery disease in women with PCOS. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 7 15 16 Chronic inflammation also contributes to endothelial dysfunction, exacerbating the development of atherosclerotic plaques, triggering the onset of CVD. 17 As such inflammation has been associated with both CVD and coronary artery disease in women with PCOS. 10 …”
Section: Introductionmentioning
confidence: 99%
“…MPs are also a type of EVs and play a fundamental role in the communication between source and target cells. Serum MPs' content can increase in variety of conditions, including PCOS (Willis et al, 2014;Carvalho et al, 2017b), prothrombotic states (Mooberry et al, 2016), and type 2 diabetes mellitus (Koga et al, 2005). Younger women with PCOS have increased concentrations of circulating annexin V-positive platelet MPs in plasma, compared with older women with PCOS (Willis et al, 2014).…”
Section: Extracellular Vesicles and Polycystic Ovary Syndromementioning
confidence: 99%
“…The relationship between MPs and the other symptoms of PCOS have not yet been established (Teede et al, 2010). MPs may serve as useful biomarkers for predicting many diseases, including PCOS and cardiovascular disease (Carvalho et al, 2017b). The ratio of ornithine to arginine in plasma derived from PCOS patients is significantly increased (Kyselova et al, 2019).…”
Section: Extracellular Vesicles and Polycystic Ovary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been demonstrated that Kiss mRNA expression is increased by TNFα, IL-6, MCP-1 and VCAM-1 in human endothelial cells, and thus, accelerates atherogenesis by enhancing the inflammatory responses (Sato et al 2017). PCOS is associated with chronic low-grade inflammation and predisposition to hemostatic and atherosclerotic complications (Carvalho et al 2017), accompanied by high plasma levels of kiss (Chen et al 2010). In contrast, the decreased expression of kiss mediates acute immune/ inflammatory stress-induced suppression of gonadotropin secretion in female rats (Iwasa et al 2008).…”
Section: Journal Of Endocrinologymentioning
confidence: 99%